2006
DOI: 10.2174/187152006776930918
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Curcumin and Its Role in Cancer Chemoprevention and Therapy

Abstract: Curcumin, a natural component of the rhizome of curcuma longa has emerged as one of the most powerful chemopreventive and anticancer agents. Its biological effects range from antioxidant, anti-inflammatory to inhibition of angiogenesis and is also shown to possess specific antitumoral activity. The molecular mechanism of its varied cellular effects has been studied in some details and it has been shown to have multiple targets and interacting macromolecules within the cell. Curcumin has been shown to possess a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
158
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(161 citation statements)
references
References 1 publication
0
158
0
3
Order By: Relevance
“…Taken together our results suggest the involvement of ATM/Chk1 in curcumin-mediated G2/M arrest and apoptosis. (Singh and Khar, 2006;Tse et al, 2007). During DNA damage, cells are blocked in G2/M phase to provide time to repair damaged DNA (Molinari, 2000;Abraham, 2001), or lead to apoptotic cell death in case of severe DNA damage .…”
Section: Curcumin Causes Dna Damage and Induces Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together our results suggest the involvement of ATM/Chk1 in curcumin-mediated G2/M arrest and apoptosis. (Singh and Khar, 2006;Tse et al, 2007). During DNA damage, cells are blocked in G2/M phase to provide time to repair damaged DNA (Molinari, 2000;Abraham, 2001), or lead to apoptotic cell death in case of severe DNA damage .…”
Section: Curcumin Causes Dna Damage and Induces Apoptosismentioning
confidence: 99%
“…Curcumin has been used in Asian countries as a dietary spice, a food-colouring agent and for the treatment of variety of ailments, including biliary disorder, anorexia, cough, diabetic wounds, hepatic disorders, rheumatism and sinusitis (Furukawa et al, 1996;Sharma et al, 2004). Although many in vitro studies have demonstrated the potential chemotherapeutic effects of curcumin against a variety of cancer cells, its clinical implementation has been a challenge because of its short half life and low bioavailability after oral administration (Cheng et al, 2001;Ireson et al, 2001;Singh and Khar, 2006). Cheng et al (2001) observed an average peak plasma concentration of 0.51 -1.77 mM (188 -652 ng ml À1 ) after an oral administration of 4 -8 g curcumin per day in patients with pre-malignant lesions.…”
Section: Chk1 Activation By Curcumin Rp Sahu Et Almentioning
confidence: 99%
“…Curcumin has also been shown to induce growth arrest and apoptosis in various cancer cell lines [67,80,154,169]. Clinical trials indicated that curcumin has no dose-limiting toxicity, and therefore, it has enormous potential for the prevention and treatment of cancer [138,166].…”
Section: Pre-clinical and Clinical Trials Of Nf-κb Inhibitorsmentioning
confidence: 99%
“…However, given the strong association between inflammation and cancer, it has been suggested that curcumin's beneficial effects on tumorigenesis are likely to largely involve the inhibition of cell signaling pathways involving nuclear factor kappa B (NFkB) (Siwak and others 2005;Singh and Khar 2006). NFkB has been linked to the initiation and progression of cancer through its ability to activate the inflammatory cascade (Karin 2006).…”
mentioning
confidence: 99%